Aggregation process of two disaster-causing jellyfish species, Nemopilema nomurai and Aurelia coerulea, at the intake area of a nuclear power cooling-water system in Eastern Liaodong Bay, China - Wang, Xiaocheng; Jin, Qingqing; Yang, Lu; Jia, Chuan; Guan, Chunjiang; Wang, Haining; Guo, Hao (Frontiers in Marine Science, 2023)
The intake safety of nuclear power cooling-water systems (NPCSs) is an important aspect of operational safety of nuclear power plants (NPPs). The blockages caused by aberrant outbreaks of various aquatic organisms have seriously affected operational safety. Large jellyfish constitute the main groups of marine organisms responsible for these blockages. The processes of aggregation and the relationships of two major disaster-causing scyphozoan jellyfish species, Nemopilema nomurai and Aurelia coerulea, with four environmental factors at the intake area of an NPCS in Eastern Liaodong Bay, China, were investigated in 2019 and 2020. The findings revealed that A. coerulea ephyrae were present in the surrounding ports in mid-May; however, N. nomurai ephyrae were absent during the survey period in this study, and the medusae of N. nomurai started appearing from late May. The individual growth and relative biomass (RB) of the jellyfish increased rapidly from late June to July and decreased rapidly thereafter, in September. The RB of N. nomurai was highly correlated to the sea surface temperature (SST) and levels of dissolved oxygen (DO) in the region. The RB increased with increasing SST and decreased at increasing DO levels. The RB of A. coerulea was significantly negatively correlated with that of N. nomurai, and the peak biomass of the two species alternated over time, which could be attributed to the fact that the jellyfish species share similar ecological niches. The bell diameters were significantly positively correlated with the individual wet weights, and the value of one could be inferred from the value of the other. Although the processes of jellyfish aggregation are attributed to several factors, including interactions with environmental factors and human activities, such as fishing, the results obtained in this study would serve as an important reference and provide a basis for the prevention of jellyfish blooms in waters adjacent to NPPs. The prevention and control of jellyfish disasters at the intake area of NPCSs are not only local concerns. Therefore, remediation from the source combined with the maximum utilization of social resources for monitoring and early warning would immensely improve the efficacy of such preventive strategies.